Are we blind to injuries in the visually impaired? A review of the literature. Issue 2 (1st June 2002) - Legood, R; Scuffham, P; Cryer, C
Abstract : Objectives: To review the literature on the risks and types of injuries associated with visual impairment, and to identify pertinent areas for future research. Methods: A search of bibliographic databases was conducted in April 2000 for studies published since 1980 and selected studies that met two or more of the following criteria: formal ophthalmic assessment was used; adjustment for confounding variables; large sample size including numbers of visually impaired; and clear definitions and outcomes. Results: Thirty one studies were selected. The majority of these studies (20) assessed falls (including eight on hip fracture and four on multiple falls), eight studies reported traffic related injuries, and three studies assessed occupational injury. The evidence on falls, which relate predominantly to older people, suggests that those with reduced visual acuity are 1.7 times more likely to have a fall and 1.9 times more likely to have multiple falls compared with fully sighted populations. The odds of a hip fracture are between 1.3 and 1.9 times greater for those with reduced visual acuity. Studies of less severe injuries and other causes of injury were either poorly designed, underpowered, or did not exist. Conclusions: There are substantial gaps in research on both injuries to which people with visual impairment are especially susceptible and in evaluating interventions to reduce these injuries. It is recommended that in future studies the minimum data captured includes: formal ophthalmic assessment of visual fields and visual acuity, outcome measurement, control for confounders, and the costs of health care resource use and any interventions.